Genomic Characterization of 2 Cutibacterium acnes Isolates from a Surgical Site Infection Reveals Large Genomic Inversion - D. Garrett Brown; Taylor A. Wahlig; Angela Ma; Laura K. Certain; Peter N. Chalmers; Mark A. Fisher; Daniel T Leung (Case Western Reserve University, 2023)
Background: Cutibacterium acnes is a common commensal of human skin but may also present as an opportunistic pathogen in prosthetic joint and wound infections. Unfortunately, few complete genomes of C. acnes are publicly available, and even fewer are of isolates associated with infection. Here we report the isolation, characterization, and complete genomes of 2 C. acnes isolates from a surgical site infection of an elbow. Methods: We used standard microbiological methods for phenotypic characterization and performed whole genome sequencing on 2 C. acnes isolates using a combination of short-read and long-read sequencing.  Results: Antibiotic susceptibility testing showed beta-lactamase negative and low minimal inhibitory concentrations to all antibiotics tested, with the exception of metronidazole. We assembled complete genomes of the 2 isolates, which are approximately 2.5 megabases in length. The isolates belong to the single-locus sequence type (SLST) H1 and the multi-locus sequence type (MLST) IB. Both isolates have similar composition of known virulence genes, and we found no evidence of plasmids but did find phage-associated genes. Notably, the 2 genomes are 99.97% identical but contain a large genomic inversion encompassing approximately half of the genome. Conclusions: This is the first characterization of this large-scale genomic inversion in nearly identical isolates from the same wound. This report adds to the limited numbers of publicly available infection-associated complete genomes of C. acnes.